2014
DOI: 10.1002/mar.20702
|View full text |Cite
|
Sign up to set email alerts
|

How Do Salespeople Make Decisions? The Role of Emotions and Deliberation on Adaptive Selling, and the Moderating Role of Intuition

Abstract: This research explores how salespeople make decisions and what factors influence these decisions. Research in psychology suggests that, in making decisions, people use both intuition and deliberation, often relying on some degree of both processes. This study examines the impact of emotion, intuition, and deliberation on a salesperson's adaptability and resulting performance. Intuition is found to play a significant moderating role in the relationships between both deliberation and regulation of emotions on ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 120 publications
(190 reference statements)
2
28
1
2
Order By: Relevance
“…Gender, employee's Tenure with Firm, Total Work Experience, and goal completion (measured as Percentage Quota Achieved) were included in the model as control variables, since these are known to impact salespersons' attitudes and behaviors (Locander et al, 2014). The results of the structural model, illustrated in Fig.…”
Section: Testing Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender, employee's Tenure with Firm, Total Work Experience, and goal completion (measured as Percentage Quota Achieved) were included in the model as control variables, since these are known to impact salespersons' attitudes and behaviors (Locander et al, 2014). The results of the structural model, illustrated in Fig.…”
Section: Testing Of Hypothesesmentioning
confidence: 99%
“…To test the stated hypotheses, a structural equation model (SEM) with AMOS 21 ML method was run, since SEM provides the flexibility to test several relationships simultaneously. Gender, employee's Tenure with Firm, Total Work Experience, and goal completion (measured as Percentage Quota Achieved) were included in the model as control variables, since these are known to impact salespersons' attitudes and behaviors (Locander et al, 2014). The results of the structural model, illustrated in Fig.…”
Section: Testing Of Hypothesesmentioning
confidence: 99%
“…Emotions generally influence decision-making (Lerner et al, 2015) and are central to "marketing exchanges and relationships" (Bagozzi, Gopinath, and Nyer, 1999). Because research on the role of emotions in a buyer-supplier relationship is just at its emerging phase (Locander, Mulki, and Weinberg, 2014) our study contributes to understanding the role of emotions in decision making under threat.…”
Section: Theoretical Contributionsmentioning
confidence: 97%
“…Mulki et al (2015) found ROE to be positively associated with job performance. Also focusing on a single EI dimension, Locander et al (2014) found ROE to have an indirect association with general job performance through adaptive selling.…”
Section: Ei Dimensions and Job Performancementioning
confidence: 97%